Improvements in Wintertime Surface Temperature Variability in the Community Earth System Model Version 2 (CESM2) Related to the Representation of Snow Density. (2nd April 2022) - Simpson, Isla R.; Lawrence, David M.; Swenson, Sean C.; Hannay, Cecile; McKinnon, Karen A.; Truesdale, John E.
Abstract: The Community Earth System Model (CESM) is widely used for the prediction and understanding of climate variability and change. Accurate simulation of the behavior of near surface air temperature ( T 2 m ) is critical in such a model for addressing societally relevant problems. However, previous versions of CESM suffered from an overestimation of wintertime T 2 m variability in Northern Hemisphere (NH) land regions. Here, it is shown that the latest version of CESM (CESM2) exhibits a much improved representation of wintertime T 2 m variability compared to its predecessor and it now compares well with observations. A series of targeted experiments reveal that an important contributor to this improvement is the local effects of changes to the representation of snow density within the land surface component. Increased snow densities in CESM2 lead to enhanced conductance of the snow layer. As a result, larger heat fluxes across the snow layer are induced in the presence of T 2 m anomalies, leading to a greater dampening of surface and near surface atmospheric temperature anomalies. The implications for future projections with CESM2 are also considered through comparison of the CESM1 and CESM2 large ensembles. Aligned with the reduction in surface temperature variability, compared to CESM1, CESM2 exhibits reduced ensemble spread in future projections of NH winter mean temperature and a smaller decline in daily wintertime T 2 m variability under climate change. Overall, this improvement has increased the accuracy of CESM2 as a tool for the study of wintertime T 2 m variability and change. Plain Language Summary: A societally relevant quantity that is predicted by Earth System Models is near surface air temperature ( T 2 m ). Accurate simulation of this quantity requires accurate representation of atmospheric circulation, boundary layer processes and land‐atmosphere interaction. Here we show substantial improvements in the representation of wintertime T 2 m variability in the latest version of the Community Earth System Model and isolate the roles of different aspects of the model development. Increases in the density of snow in the new model are shown to reduce T 2 m variability. Snow density governs the heat fluxes induced across the snow layer via conductance and increased snow density in the model has increased the ability of heat fluxes across the snow layer to dampen T 2 m variability. The implications of this change for future climate projections are explored and it is found that CESM2 exhibits a reduced uncertainty in future projections of mean T 2 m over Northern Hemisphere land regions, as might be expected given the reduced sampling uncertainty in T 2 m due to reduced internal variability. Furthermore, wintertime T 2 m variability is expected to decrease under climate change and this decrease is larger in the older version of the model that exhibited greater T 2 m variability in its historical simulation. Key Points: Northern Hemisphere wintertime surface temperature variability was overestimated in Community Earth System Model Version 1 and is improved in Community Earth System Model Version 2 (CESM2) This improvement has arisen through an increase in snow density and associated snow conductance A reduced ensemble spread and reduced decline in daily variance is also found in future projections of surface temperature with CESM2